Preparation of long-term cycling stable ni-rich concentration–gradient NCMA cathode materials for li-ion batteries - Jeyakumar, Juliya; Seenivasan, Manojkumar; Wu, Yi–Shiuan; Wu, She–Huang; Chang, Jeng Kuei; Jose, Rajan; Yang, Chunchen (Academic Press Inc., 2023)
Nickel-rich (Ni > 90 %) cathodes are regarded as one of the most attractive because of their high energy density, despite their poor stability and cycle life. To improve their performance, in this study we synthesized a double concentration-gradient layered Li[Ni0.90Co0.04Mn0.03Al0.03]O2 oxide (CG-NCMA) using a continuous co-precipitation Taylor–Couette cylindrical reactor (TCCR) with a Ni-rich-core, an Mn-rich surface, and Al on top. The concentration-gradient morphology was confirmed through cross-sectional EDX line scanning. The as-synthesized sample exhibited excellent electrochemical performance at high rates (5C/10C), as well as cyclability (91.5 % after 100 cycles and 70.3 % after 500 cycles at 1C), superior to that (83.4 % and 47.6 %) of its non-concentration-gradient counterpart (UC-NCMA). The Mn-rich surface and presence of Al helped the material stay structurally robust, even after 500 cycles, while also suppressing side reactions between the electrode and electrolyte, resulting in better overall electrochemical performance. These enhancements in performance were studied using TEM, SEM, in-situ-XRD, XPS, CV, EIS and post-mortem analyses. This synthetic method enables the highly scalable production of CG-NCMA samples with two concentration-gradient structures for practical applications in Li-ion batteries.